Age Variation in Bitter Taste Perception in Relation to the Tas2r38 Taste Receptor Phenotype - Rossella, Negri; Andrea, Smarrazzo; Martina, Galatola; Antonietta, Maio; Paola, Iaccarino Idelson; Maura, Sticco; Carmen, Biongiovanni; Adriana, Franzese; Luigi, Greco; Davide, Risso; Gabriella, Morini (International Journal of Nutrition, 2015)
Objectives Taste sensitivity is an important determinant of food choice and differs between children and adults. This difference is probably due to several factors that constitute an individual’s phenotype. The aim of this study was to explore taste perception in relation to the TAS2R38 and CAVI (gustin) genotypes in age classes from infancy to adulthood in a Mediterranean population. Methods In this cross-sectional study we evaluated the TAS2R38 and gustin genotypes and administered a standardized PROP taste test in 705 individuals (435 adults, 270 children); the sample included 224 mother-child dyads. We also explored the acceptance and consumption of bitter and non-bitter vegetables. Results Sensitivity to bitterness was strongly related to the TAS2R38 haplotype, and we observed an intriguing relationship with age. In fact, children were more sensitive than adults with the same TAS2R38 haplotype also within mother-child dyads. The mother-child tasting differences decreased with age and became minimal when children reached adolescence. Variations in the gustin gene did not contribute significantly to the overall taste phenotype, but helped to differentiate among non-tasters. Conclusions The genetic profile of the bitter-taste receptor TAS2R38 explains most of the variance in bitter taste perception, but the related phenotype is also strongly influenced by age, also in mother-child dyads that share the same genotype. This finding is likely to have a significant impact on the complex feeding relationship between mother and child.
Keywords: Bitter perception; Food choices; TAS2R38 polymorphism; Gustin polymorphism; Mother-child dyads.